Avoidance Behavior: A Free‐Operant Lever‐Press Avoidance Task for the Assessment of the Effects of Safety Signals. Issue 1 (5th January 2015) - Fernando, Anushka B.P.; Mar, Adam C.; Urcelay, Gonzalo P.; Dickinson, Anthony; Robbins, Trevor W.
Abstract: This protocol details a free‐operant avoidance paradigm that has been developed to evaluate the relative contribution of different sources of reinforcement of avoidance behavior that may play an important role in the development and maintenance of human anxiety disorders. The task enables the assessment of the effects of safety cues that signal a period free from danger on lever‐press avoidance behavior. Avoidance behavior trained using this protocol has been shown to be sensitive to both behavioral and pharmacological manipulations and has been optimized so that it takes approximately 1 month for rats to perform at high levels of stable avoidance responding. © 2015 by John Wiley & Sons, Inc.